(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2019)
Labeo calbasu (Family Cyprinidae) was studied at DNA level to know genetic diversity within and between species. The mitochondrial cytochrome b (cyt-b) gene of L. calbasu was sequenced and compared to the corresponding sequences of other Labeo species. DNA was isolated from the tissue sample of L. calbasu using phenol: chloroform extraction method. Forward and reverse primers were designed to amplify the target region of cytochrome b gene. A standard PCR protocol was used for the amplification of the desired region. Then, the forward and reverse sequences obtained were aligned and edited to finalize a length of 510 nucleotides which was submitted to NCBI genbank database. Nucleotide BLAST of this sequence at NCBI resulted 100% sequence similarity with L. calbasu sequence of the same region of cyt-b gene. Multiple sequence alignment of the sequence with seven more Labeo species sequences revealed 120 polymorphic sites, which have been mark of diversity among the species and might be used in molecular identification of the Labeo species. A constructed phylogenetic tree has shown relationship among the Labeo species. This research demonstrated the usefulness of mitochondrial DNA-based approach in species identification. Further, the data will provide appropriate background for studying genetic diversity within-species of the Labeo species in general and of L. calbasu in particular. J. Biodivers. Conserv. Bioresour. Manag. 2019, 5(1): 25-30